Some contributions from the thinking of Franz Hinkelammert on the idea and practice of Human Rights - Sánchez Rubio, David (2025)
This paper presents five contributions of Franz Hinkelammert’s thought in the field of human rights that are interrelated and closely linked to each other: 1) an anthropological faith in the human being; 2) the criticism of utopian reason extended to the idolatrous and fetishistic processes of human production, together with the principles of impossibility of the empirical sciences and the way in which it affects the human condition; 3) the ideological inversion of human rights; 4) the categorical imperative against victimization processes; and 5) the criterion and principle of production, reproduction and development of human life in its circuit with Nature.